PENGARUH KONSUMSI SARI KURMA (DATES SYRUP) TERHADAP KONSENTRASI LIPID PEROKSIDA SELAMA LATIHAN AEROBIK AKUT BAGI PEMULA - Budi Hernawan; Zaenal Muttaqien Sofro; Sri Lestari Sulistyorini (Biomedika, 2019)
The increase of energy need during physical exercise of aerobics will increase the need of oxygen, and therefore it can cause free radicals increase. Naturally, endogenous antioxidants can overcome the increase of free radicals. However, if the antioxidants formation which is not comparable with the occurrence of free radicals will cause the occurrence of oxidative stress. So it requiered antioxidants from the outside to take care of it. This research aims to study differences in oxidative stress between groups that consume dates syrup and groups that does not consume date syrup during acute aerobic exercise for untrained men through the lipid peroxide concentration with plasma malondialdehyde (MDA) indicators. This research design is experimental research, non-randomized pre-post test control group design. The subjects divided into two groups namely the group of dates syrup and the group of fresh water. Both group were given treatment of acute aerobic exercise with medium intensity every 2 days for 28 days. Blood samples taken before the aerobic exercise, after the 1st, 7th, and 14th aerobic exercise, and then were checked its plasma MDA levels. Data analysis was done with independent t-test. Analysis of plasma MDA levels t-test showed that there was no difference between the group of dates syrup and the group of fresh water. Plasma MDA levels of the group consuming dates syrup was not much different compared to the group not consuming dates syrup during aerobic exercise with medium intensity for untrained men.Keywords: acute aerobic exercise, untrained men, dates syrup, plasma MDA